(untitled) (CIPEEX, 2026)
Introduction: Down Syndrome (DS) is an aneuploidy resulting from the trisomy of chromosome 21, associated with muscle hypotonia, postural instability, and deficits in motor control, factors that increase the risk of falls. In this context, virtual reality (VR) has emerged as a promising strategy in rehabilitation, as it integrates motor and cognitive stimuli in interactive environments. Objective: The aim was to analyze the effects of a VR training protocol on functional mobility, dynamic balance, and physical performance in individuals with DS. Methods: Five participants with DS underwent a VR intervention consisting of a total of 16 sessions lasting 50 minutes each. The assessment was carried out using the G-WALK inertial system, employing three validated tests: Timed Up and Go (TUG) for measuring functional mobility; 6-Minute Walk Test (TC6) for analyzing cardiorespiratory fitness; and Countermovement Jump for evaluating muscle power. There was clinical improvement observed in the TUG, with a reduction in the average total time (from 15.1s to 12.8s), indicating gains in dynamic balance and neuromuscular efficiency. However, no significant changes were observed in muscle power, and the results of the TC6 showed high variability, including a reduction in the average distance covered. Results: It is concluded that training with VR demonstrated potential to enhance functional mobility and dynamic balance in individuals with SD, but did not promote consistent gains in strength or cardiorespiratory capacity. Further studies with larger samples and greater methodological rigor are needed to consolidate the efficacy of this intervention.